Ultra high density imaging arrays in diffuse optical tomography for human brain mapping improve image quality and decoding performance - Zachary E. Markow; Jason W. Trobaugh; Edward J. Richter; Kalyan Tripathy; Sean M. Rafferty; Alexandra M. Svoboda; Mariel L. Schroeder; Tracy M. Burns-Yocum; Karla M. Bergonzi; Mark A. Chevillet; Emily M. Mugler; Adam T. Eggebrecht; et al. (Scientific Reports)
Abstract Functional magnetic resonance imaging (fMRI) has dramatically advanced non-invasive human brain mapping and decoding. Functional near-infrared spectroscopy (fNIRS) and high-density diffuse optical tomography (HD-DOT) non-invasively measure blood oxygen fluctuations related to brain activity, like fMRI, at the brain surface, using more-lightweight equipment that circumvents ergonomic and logistical limitations of fMRI. HD-DOT grids have smaller inter-optode spacing (~ 13 mm) than sparse fNIRS (~ 30 mm) and therefore provide higher image quality, with spatial resolution ~ 1/2 that of fMRI, when using the several source-detector distances (13–40 mm) afforded by the HD-DOT grid. Herein, simulations indicated reducing inter-optode spacing to 6.5 mm, creating a higher-density grid with more source-detector distances, would further improve image quality and noise-resolution tradeoff, with diminishing returns below 6.5 mm. We then constructed an ultra-high-density DOT system (6.5-mm spacing) with 140 dB dynamic range that imaged stimulus-evoked activations with 30–50% higher spatial resolution and repeatable multi-focal activity with excellent agreement with participant-matched fMRI. Further, this system decoded visual stimulus position with 19–35% lower error than previous HD-DOT, throughout occipital cortex.